Examination of the histopathological effects of proximal tubal occlusion procedure on rat ovaries: An experimental study - Çelik, Dr. Aygen; Atılgan, Remzi; Haliloğlu, Berna; İlter, Erdin; Gündüz, Tonguç; Akpolat, Nusret; Sapmaz, Ekrem (Maltepe University, 2011)
Objective: Examination of the effects of unilateral proximal tubal oclusion procedure by bipolar electrical coagulation on rat's ovarian histopathology at the first and six months. Material and Methods: Adult 28 Winstar albino rats at eustrous phase randomly divided into 4 groups. G1 n=7 : Left oopherectomy, one month after laparatomy. G2 n=7 : Left oopherectomy, one month after proximal tubal oclusion. G3 n=7 : Left oopherectomy, six months after laparatomy. G4 n=7 : Left oopherectomy, six months after proximal tubal oclusion. Left ovary specimens fixed with formaldehyde, dyed with Hematoxylen-Eosin and ovarian reserve examined. The number of atretic follicles, corpus luteum and corpus albicans determined. Angiogenesis in corpus luteum and presence of ovarian stromal fibrosis examined. G1and G2 were compared with G3 and G4. Statistical analysis of ordinal results were examined by Mann Whitney U test and nominal results by x2 test f. P0.05, Mann Whitney U test . Angiogenesis regression in corpous luteum were lower in both G2 and G4. No macroscopic or microscopic cyst formation obtained in all groups. Conclusion: Proximal tubal occlusion procedure by bipolar coagulation has no harmful effect on rat oavarian histopathology at both early and late period.

Amaç: Bipolar koter kullanılarak yapılan unilateral proksimal tubal oklüzyon işleminin birinci ve altıncı aylarda rat over histopatolojisi üzerine etkilerinin incelenmesi. Yöntem: Erişkin 28 Wistar albino rat östrus fazında rastgele 4 gruba ayrıldı. G1 n=7 : Batın açılıp kapatılan ve 1 ay sonra sol ooferektomi yapılan grup. G2 n=7 : Sol proksimal tubal oklüzyon yapılıp 1 ay sonra sol ooferektomi yapılan grup. G3 n=7 : Batın açılıp kapatılan ve 6 ay sonra sol ooferektomi yapılan grup. G4 n=7 : Sol proksimal tubal oklüzyon yapılıp 6 ay sonra sol ooferektomi yapılan grup. Sol over örnekleri formaldehitle tespit edildi. Hematoksilen Eozin ile boyanan preparatlarda over folikül rezervi saptandı. Atretik foliküllerin sayısı, corpus luteum, corpus albicans tespit edildi. Corpus luteum içi anjiogenesiz varlığındaki gerileme ve ovaryan stromada fibrozis varlığı incelendi. Overdeki folikül kisti sayıldı. G1-G2 ile G3-G4 ile karşılaştırıldı. Ordinal veriler için Mann Whitney U testi, nominal veriler için x2 testleri kullanıldı. p0.05, Mann Whitney U test . Corpus luteum içi anjiogenezisdeki gerileme G2 ve G4'de anlamlı olmamakla birlikte azalmıştı. Hiçbir grupta makroskobik veya mikroskobik kist gelişmedi Sonuç: Ratlarda bipolar koter kullanılarak yapılan unilateral proksimal tubal okluzyon işlemi, erken ve geç dönemde over histopatolojisi üzerine herhangi bir zararlı etki yapmamıştır.
Proksimal tubal oklüzyon işleminin rat over histopatolojisi üzerine etkilerinin incelenmesi: Deneysel çalışma